The Evolution of Prop Firms: How Innovation in Trader Evaluation is Redefining the Sector - Lokier , Saul; Montalvo, Diego Andres Cevallos (RCMOS - Revista Científica Multidisciplinar O Saber, 2025)
This paper analyzes the cyclical transformations of the financial sector, driven by technological innovation, market changes, and regulations. Among the segments that have evolved the most in recent decades is the foreign exchange (Forex) market, characterized by its global liquidity and decentral structure. In this context, Proprietary Trading Firms (Prop Firms) are emerging as innovative business models by allowing independent traders to operate with the company's capital in exchange for a share of the profits. The article highlights that, although the concept of proprietary trading is ancient, modern Prop Firms represent a complete reformulation of the model, marked by digitalization, global access, and the sophistication of risk assessment and management systems. The research, both technical and historical in nature, examines how these innovations are redefining both the Prop Firm sector and the broader fintech and capital management ecosystems, consolidating them as central players in a constantly transforming market.